2021
DOI: 10.3390/math10010041
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Student Engagement on Mathematical Achievement among Secondary School Students

Abstract: Student engagement is a multidimensional construct that predicts learning performance. However, student engagement receives limited attention, especially in mathematics. Thus, this study conducts a survey to determine the influence of student engagement on mathematical achievement. Stratified random sampling was employed to select secondary school students (n = 1000). Questionnaires and end-of-year examination grades were collected as data on student engagement and respective mathematics achievement. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 71 publications
4
22
0
Order By: Relevance
“…Thus, students at different academic levels may have a negative or positive attitude towards mathematics due to fundamentally different reasons. Yet, other studies show the existence of a positive relationship between attitude and achievement in mathematics (e.g., Berger et al, 2020;Chen et al, 2018;Davadas and Lay, 2020;Grootenboer and Hemmings, 2007;Hwang and Son, 2021;Lipnevich et al, 2011;Ma, 1997;Maamin et al, 2022;Mazana et al, 2018;Mulhern and Rae, 1998;Opolot-okurut, 2010;Sandman, 1980;Tapia, 1996). From the above studies, it appears that multiple factors ranging from students' to teachers' classroom instructional practices may influence students' attitudes towards, and achievement in mathematics.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, students at different academic levels may have a negative or positive attitude towards mathematics due to fundamentally different reasons. Yet, other studies show the existence of a positive relationship between attitude and achievement in mathematics (e.g., Berger et al, 2020;Chen et al, 2018;Davadas and Lay, 2020;Grootenboer and Hemmings, 2007;Hwang and Son, 2021;Lipnevich et al, 2011;Ma, 1997;Maamin et al, 2022;Mazana et al, 2018;Mulhern and Rae, 1998;Opolot-okurut, 2010;Sandman, 1980;Tapia, 1996). From the above studies, it appears that multiple factors ranging from students' to teachers' classroom instructional practices may influence students' attitudes towards, and achievement in mathematics.…”
Section: Introductionmentioning
confidence: 97%
“…Mathematicians have attempted to research and understand affective variables that significantly influence students' attitude towards mathematics (e.g., Barmby et al, 2008;Davadas and Lay, 2020;Di Martino and Zan, 2011;Evans and Field, 2020;Grootenboer and Hemmings, 2007;Hannula, 2002;Maamin et al, 2022;Marchis, 2011;Pongsakdi et al, 2019;Yasar, 2016;Zan et al, 2006). Some researchers have gone ahead to ask fundamental questions on whether or not students' attitude towards mathematics is a general phenomenon or dependent on some specific variables.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there was not an important difference in mean scores of students at public schools and private schools on surface strategies, interest, attentiveness and diligence. So behavioural engagement of students in public and private schools is almost the same (Maamin, Maat & Iksan, 2021) Researchers has also investigated engagement of secondary school students and they have found positively correlated all factors of students' academic engagement (Rotgans, & Schmidt, 2011). A comparison between public and private school students on self-regulated learning has shown difference in public and private school students on goal setting, environment structuring, help seeking, self-evaluation and self-regulation (Asim, & Farooq, 2021 On the other hand, there was not important difference in mean scores of public teacher schools scores on task strategies, time management and cognitive strategy use.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, students at different academic levels may have negative or positive attitude towards mathematics due to fundamentally different reasons. Yet, some empirical studies have shown existence of significant relationships between students’ attitude and performance in mathematics (e.g., Berger et al, 2020; Chen et al, 2018; Davadas & Lay, 2020; Grootenboer & Hemmings, 2007; Hwang & Son, 2021; Lipnevich et al, 2011a; Ma, 1997; Maamin et al, 2022; Mazana et al, 2018b; Mulhern & Rae, 1998; Opolot-okurut, 2010; Sandman, 1980; Tapia, 1996). From the above studies, it appears that multiple factors ranging from students’ demographic factors to teachers’ classroom instructional practices influence students’ attitude towards learning mathematics.…”
Section: Introduction and The Concept Of Students’ Attitude Towards M...mentioning
confidence: 99%
“…Thus, students at different academic levels may have negative or positive attitude towards mathematics due to fundamentally different reasons. Yet, some empirical studies have shown existence of significant relationships between students' attitude and performance in mathematics (e.g., Berger et al, 2020;Chen et al, 2018;Davadas & Lay, 2020;Grootenboer & Hemmings, 2007;Hwang & Son, 2021;Lipnevich et al, 2011a;Ma, 1997;Maamin et al, 2022;Mazana et al, 2018b;Mulhern & Yet, mathematical word problems are intended to help learners to apply mathematics beyond the classroom in solving real-life-world problems. Verschaffel et al (2020) and Boonen et al (2016) have argued that mathematics word problems are difficult, complex, and pause comprehension challenges to most learners.…”
Section: Introduction and The Concept Of Students' Attitude Towards M...mentioning
confidence: 99%